2022
DOI: 10.12659/msm.936246
|View full text |Cite
|
Sign up to set email alerts
|

Curative Analysis of Patients with Hepatocellular Carcinoma Using Transcatheter Arterial Chemoembolization Combined with Radiofrequency Ablation

Abstract: Background Transcatheter arterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) can improve the survival of patients with hepatocellular carcinoma (HCC). The purpose was to explore the characteristics of high-risk and low-risk groups of HCC patients receiving combination therapy using a decision tree model. Material/Methods This retrospective cohort study investigated HCC patients treated with a combination of TACE and RFA at our hospital from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several recent studies, however, have suggested that patients with symptomatic HCC without MVI or EHS should not be regarded as having advanced-stage disease. Furthermore, patients with advanced HCC without MVI or EHS in a real-world setting have frequently been treated with locoregional therapy, such as transarterial chemoembolization (TACE) (6)(7)(8)(9)(10). The efficacy of TACE, however, has been insufficiently defined, and factors associated with prognosis in patients treated with TACE remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies, however, have suggested that patients with symptomatic HCC without MVI or EHS should not be regarded as having advanced-stage disease. Furthermore, patients with advanced HCC without MVI or EHS in a real-world setting have frequently been treated with locoregional therapy, such as transarterial chemoembolization (TACE) (6)(7)(8)(9)(10). The efficacy of TACE, however, has been insufficiently defined, and factors associated with prognosis in patients treated with TACE remain unclear.…”
Section: Introductionmentioning
confidence: 99%